A Seasonal Comparison of the Effectiveness of Parent Engagement on Student Literacy Achievement - Hillier, Cathlene (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2021)
Parent engagement is often promoted as a remedy for reducing achievement gaps between students from high socio-economic and low socio-economic backgrounds. However, researchers have found mixed results when examining parent engagement and student outcomes. Drawing on a study investigating the effectiveness of summer literacy camps offered by schools in Ontario, I compare the influence of parent engagement on two outcomes: (1) spring snapshot of cumulative learning, and (2) summer literacy growth/loss. In considering summer learning in regression analysis, I aim to investigate the effect of parent engagement without the influence of schools during the academic year. Out of 14 parent engagement measures, I find only three (parents’ aspirations, home resources, discussions of school with children) are positive predictors of spring literacy outcomes and that none predict summer literacy growth/loss. Family socio-economic status remains a powerful predictor of achievement for both outcomes. I interpret my findings within three proposed mechanisms of parent engagement: cultivation ethic, realist reaction, and expressive logic.